REQUIREMENTS FOR A HEALTHY LIFESTYLE (Academicia Globe: Inderscience Research, 2021)
In this article, the author analyzes the concept of a healthy lifestyle in terms of current problems, the factors affecting the health of the population and especially human health, the elements of a healthy lifestyle as a system in maintaining public health.